The Crime Reducing Effect of Education - Olivier Marie
In this paper, we present evidence on empirical connections between crime and education, using various data sources from Britain. A robust finding is that criminal activity is negatively associated with higher levels of education. However, it is essential to ensure that the direction of causation flows from education to crime. Therefore, we identify the effect of education on participation in criminal activity using changes in compulsory school leaving age laws over time to account for the endogeneity of education. In this causal approach, for property crimes, the negative crime-education relationship remains strong and significant. The implications of these findings are unambiguous and clear. They show that improving education can yield significant social benefits and can be a key policy tool in the drive to reduce crime.Crime, education, offenders